Answer :

Given A and B are symmetric matrices


A’ = A --- 1


B’ = B ---- 2


Now (AB – BA)’ = (AB)’ – (BA)’


=B’A’ – A’B’


[’ = B’A’ ]


= BA – AB [Using 1 and 2]


(AB – BA)’ = - (AB - BA)


AB-BA is a skew symmetric matrix.

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

<span lang="EN-USMathematics - Exemplar

<span lang="EN-USMathematics - Exemplar

Fill in the blankMathematics - Exemplar

Fill in the blankMathematics - Exemplar

Fill in the blankMathematics - Exemplar

If A, B are squarMathematics - Exemplar

Fill in the blankMathematics - Exemplar

Fill in the blankMathematics - Exemplar

Express the folloMathematics - Board Papers

Fill in the blankMathematics - Exemplar